From Contracts to Compliance? An Early Look at Implementation Under China’s New Labor Legislation Law - Ho, Virginia E. Harper (Columbia Journal of Asian Law, 2009)
In 2008, three new primary labor laws took effect in China that together represent the first major retooling of its labor legislation in fifteen years: the Labor Contract Law, the Labor Dispute Mediation and Arbitration Law, and the Employment Promotion Law. The new laws have attracted widespread attention from the international business communi- ty, labor advocates, and observers of China’s ongoing legal reforms. However, whether the legislation can overcome and resolve fundamental implementation barriers remains largely the subject of speculation and debate. This article offers a preliminary answer.